Building pre-service teachers’ resilience through Service-Learning: an explanatory sequential mixed methods study - Marta Sánchez-Jiménez; Marta Sánchez-Jiménez; María Maravé-Vivas; Jesús Gil-Gómez; Celina Salvador-Garcia (Frontiers in Psychology)
University education should not be limited to mere instruction in professional skills but should foster the holistic development of students. This approach is particularly necessary in a changing society marked by rapid technological advances, labor transformations and global challenges. Therefore, higher education must offer students the opportunity to develop strategies to protect and improve their mental health. Within the concept of mental health is resilience, which enables the mobilization of internal and external resources to cope with and learn from challenging situations, managing change and uncertainty more effectively. Using a mixed methodological approach based on an explanatory sequential design, the present study aims to determine the effect of Service-Learning on the levels of resilience of students enrolled in the degree of Physical Activity and Sport Sciences at the Universitat Jaume I in Spain. To this end, the Resilience Questionnaire for Adults (RQA) was administered before and after a Service-Learning program. The reflection diaries written by the participants (n = 54) were analyzed too. The quantitative results show an improvement, which is significant for the “adaptative” and “tolerance” components of resilience, while the qualitative phase allows us to understand these results. In general, the findings point to the development of resilience among participants, which is a result consistent with previous literature suggesting that Service-Learning can be an adequate approach to foster the acquisition of skills present in the resilience construct, while favoring learning and fostering social compromise.